Disease knowledge and preferences for disclosure of in- formation in patients with rheumatoid arthritis - Pauletti Gonçalves, Rafael; Carolina Diana Simões, Maria; Viana Pereira, Renata; Barbella Saba, Amine; Santos Novaes, Gilberto (Seven Editora, 2023)
Objectives: To verify the level of knowledge about rheumatoid arthritis (RA) and the patient’s preferences for disclosure of information by the physician in patients with RA, we compared with a control group of patients without RA. Methods: We evaluated 30 patients diagnosed with RA, according to the ACR criteria, and 30 patients with other diseases pared for age, gender, level of education, and disease duration followed in an Out- Patient Service. Clinical-demographic data as age, gender, level of education, and disease duration were obtained from both groups. We applied questionnaires to evaluate the level of knowledge about RA (10 questions) with answers yes or no, and the patient’s preference for disclosure of information by the physician (4 questions) in a Likert scale from a) strongly agree to e) strongly disagree to both groups. The questionnaires were validated for Portuguese by the method of translation and re-translation. The Ethical Committee at the Pontifical Catholic University approved the study, and we obtained informed consent from all patients. When appropriated, statistical analysis of the data included the chi-square test and student’s t-test. The significance level was 0.05. Results: Over 30 patients with RA, 27 patients (90%) were women, the mean age was 50.8 years old, with a mean of 3.03 years on school, and mean disease duration of 10.6 years. The knowledge about RA as a mean reached 5.36 points in 10 as a correct answer in RA patients and 5.13 in controls. Concerning the patient’s preference for disclosure of information by the physician, the results varied between 23.3% and 90% in the answers strongly agree or agree in the group of RA patients and 6.6% to 90% in controls. In a specific question about "patients with RA should not play a role in managing their disease because the physician is the one in charge," 56.6% of RA patients agreed, and 46,6% of controls too. Only one question about patient’s preference for disclosure of information by the physician “When there is more than one way to treat a problem, I should be told about each one” there was a trend to differ between the controls and the RA patients (p=0.06). The analysis of the results showed no statistical difference in answers to the questionnaires between RA patients and controls. Conclusion: Our results showed that RA patients, compared to control patients with other non-rheumatic diseases, do not show differences to the level of knowledge about rheumatoid arthritis (RA) and the patient’s preferences for disclosure of information by the physician. DOI: 10.56238/pacfdnsv1-017